When rudeness goes home: the impact of supervisor incivility on employees’ work–family conflict - Hassan Imam; Naveed Bilal; Tomoki Sekiguchi (Future Business Journal)
Abstract This study uses the frustration-aggression theory to examine how supervisor incivility relates to employee interpersonal incivility toward customers and co-workers and work–family conflict. Work–family conflict refers to the incompatibility between the demands and responsibilities of an individual’s work role and their family role. Service employees from the banking industry (N = 750) participated in the study’s daily multisource questionnaires over a continuous two-week period. The study’s findings, based on multilevel structural equation modeling, show that supervisors’ hostility toward subordinates increases employee interpersonal deviance toward customers and co-workers, as well as work–family conflict. Additionally, the study found in a parallel mediation that the association between supervisor-initiated incivility and work–family conflict is mediated by employee interpersonal deviance toward co-workers and customers. These findings indicate the detrimental effects of incivility from supervisors on both the workplace and employees’ personal lives. The study suggests that workplace incivility causes a negative spiral of mistreatment where a target of incivility may respond by mistreating other, resulting in a toxic work environment. However, organizations can mitigate the negative effects of incivility and promote productivity and success for employees and organization by investing in employee well-being and creating a respectful work culture.